Study of the diversity of culturable actinomycetes in the North Pacific and Caribbean coasts of Costa Rica - Solano Arias, Godofredo (2009)
In this study, 137 actinomycetes were isolated from subtidal marine sediments in the North Pacific and Caribbean coasts of Costa Rica. Bioinformatics analysis of the 16S rRNA gene sequences assigned the isolates to 15 families and 21 genera. Streptomyces was the dominant genus while the remaining 20 genera were poorly represented. Nearly 70% of the phylotypes presented a coastal-restricted distribution whereas the other 30% were common inhabitants of both shores. The coastal tropical waters of Costa Rica showed a high diversity of actinomycetes, both in terms of the number of species and phylogenetic composition, although significant differences were observed between and within shores. The observed pattern of species distribution might be the result of several factors including the characteristics of the ecosystems, presence of endemic species and the influence of terrestrial runoff.